2003
DOI: 10.1016/s0014-5793(03)00510-6
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of type II procollagen pre‐mRNA in chondrocytes is oppositely regulated by BMP‐2 and TGF‐β1

Abstract: Type II collagen is the major protein of cartilage and is synthesized as a procollagen in two forms (IIA and IIB), generated by di¡erential splicing of the gene primary transcript. Previous studies have indicated that only type IIB is expressed in di¡erentiated chondrocytes. Here, we examined the e¡ects of bone morphogenetic protein (BMP)-2 and transforming growth factor (TGF)-L L1 on the expression of IIA and IIB forms expressed in de-di¡erentiated chondrocytes grown in monolayer. Our results demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 42 publications
4
34
0
1
Order By: Relevance
“…As a first attempt to compare the capabilities of BMP-2 and TGF-b1 to direct redifferentiation of chondrocytes, we used embryonic mouse chondrocytes, a cell model routinely used in our laboratory. [3][4][5][6][7][8] We found that BMP-2 was more effective than TGF-b1 to restore the chondrogenic character of chondrocytes, as judged by the re-expression of specific chondrocytic markers such as Sox9, a10 integrin subunit, and type IIB procollagen isoform. 5 However, this redifferentiation occurred to a certain extent only, since type I collagen expression persisted indifferently after the addition of BMP-2 or TGF-b1.…”
Section: Introductionmentioning
confidence: 85%
“…As a first attempt to compare the capabilities of BMP-2 and TGF-b1 to direct redifferentiation of chondrocytes, we used embryonic mouse chondrocytes, a cell model routinely used in our laboratory. [3][4][5][6][7][8] We found that BMP-2 was more effective than TGF-b1 to restore the chondrogenic character of chondrocytes, as judged by the re-expression of specific chondrocytic markers such as Sox9, a10 integrin subunit, and type IIB procollagen isoform. 5 However, this redifferentiation occurred to a certain extent only, since type I collagen expression persisted indifferently after the addition of BMP-2 or TGF-b1.…”
Section: Introductionmentioning
confidence: 85%
“…It is well known that cultured chondrocytes readily dedifferentiate in monolayer culture with increasing expression levels of COL1A1 across passage and decreases in COL2A1 across passage (Darling and Athanasiou 2005a;Darling and Athanasiou 2005b;Valcourt et al 2003). Cultured chondrocytes will attach and maintain their native rounded morphology when plated on tissue culture plastic but will then slowly flatten and occupy larger amounts of surface area in monolayer culture.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen IIA is broadly expressed in embryonic or nonchondrogenic tissues as well as prechondrocytes and mesenchymal cells. The expression of collagen IIB, an isoform lacking a 69 amino acid cysteine-rich domain encoded by exon 2 is specifically localized in differentiating and adult chondrocytes, indicating the differentiation into functional chondrocytes (Ng et al, 1993;Sandell et al, 1994;Valcourt et al, 2003). Moreover, the high expression level of total collagen II and an isoform IIB in a primary culture of chondrocytes dramatically decreased within a few days followed by the first passage, whereas the expression level of collagen IIA relatively increased (Valcout et al, 2003).…”
Section: Discussionmentioning
confidence: 99%